79 Prognostic significance of mitral regurgitation following acutely revascularised st-segment elevation myocardial infarction. (June 2018) - Hughes, Rosie; Curran, Matthew; Rahbi, Hazim; Johnson, Thomas; Strange, Julian; Dorman, Stephen; Nightingale, Angus; Dastidar, Amardeep
Abstract : Background: Ischaemic mitral regurgitation (MR) is a known complication of ST elevation myocardial infarction (STEMI). There is a paucity of evidence on the impact of acutely revascularised STEMI on the mitral valve. The current ESC and ACC guidelines do not specifically advise a management strategy in this cohort. The aim of this study is to delineate the effect of STEMI on the mitral valve, identify predictors of MR and compare mortality between these groups. Methods: In this observational registry study, we analysed 1122 consecutive patients presenting with STEMI who underwent primary PCI between April 2014 and April 2016. We identified predictors of significant MR (moderate or severe) and compared the mortality risk in MR group vs no MR group. Statistical analysis was done on SPSS. Results: Of the 1122 patients identified at baseline (mean age 64±13 years, and 76% male), 94 were excluded due to missing echo data. 62 patients (6%) were found to have significant MR. Patients' with significant MR were on average 10 years older than patients with no MR (95% CI =6.7 –−13.13 ; p <0.001). 18% of patients with LVEF <40% had significant MR compared to 3% with EF >40% (p<0.001). Although 76% of the sample population were male, females were shown to have a proportionally higher prevalence of MR and higher all-cause mortality (p =0.0179 ; p =0.0048 ) compared with males. All-cause mortality at the time of data collection was 19% in MR group vs 5% in no MR group. On a multivariate analysis; age, LV ejection fraction, renal impairment and non-smoker status were all shown to be significant predictors for ischaemic MR. Over a mean follow up of 2.3 years, 8% of the patients died, with significantly higher mortality in moderate-severe MR group compared with no MR group (Log rank 13.4, p<0.001). (Kaplan Meier graph). Conclusion: Acute MR was found to be a significant predictor of mortality following STEMI. 3% of patients with LVEF >40% were found to have significant MR and may benefit from a repeat echocardiogram at follow-up thereby guiding future management. Prospective multicenter trials are warranted to confirm the finding.